Vesomni improves the quality of life in men with lower urinary tract symptoms in routine clinical practice in Europe. Issue 3 (22nd February 2019) - Rees, Jonathan; Foley, Steve; Huang, Moses; Rosa Arias, José; Skoumal, René; Walters, Carien; Yavuz, Yalcin; De Wachter, Stefan
Abstract: Aim: To evaluate the impact of Vesomni/Urizia/Volutsa, a fixed‐dose combination tablet containing 6 mg solifenacin (antimuscarinic) and 0.4 mg tamsulosin (α‐blocker), on health‐related quality of life (HRQoL) and treatment satisfaction in men with lower urinary tract symptoms (LUTS) associated with benign prostatic hyperplasia (BPH) in routine clinical practice. Methods: EUROPA was a noninterventional study of men with LUTS/BPH not responding to monotherapy who were prescribed Vesomni in routine clinical practice. Data were collected retrospectively (1 year) and prospectively (1 year). Assessments were performed at baseline, weeks 4 to 8, weeks 9 to 18 (optional), weeks 19 to 39 (optional), and Weeks 40 to 52. The primary endpoint was change from baseline in HRQoL, as assessed by the Overactive Bladder Questionnaire (OAB‐q) symptom bother subscale score. Change from baseline in OAB‐q total and coping, sleep, and social interaction subscale scores, treatment satisfaction‐visual analog scale (TS‐VAS), International Prostate Symptom Score (IPSS), and European Quality of Life 5‐Dimension‐5‐Level (EQ‐5D‐5L) questionnaire were also evaluated. Results: Five hundred and eighty‐nine patients were enrolled. The mean changes in adjusted mean (95% confidence interval [CI]) OAB‐q symptom bother subscale scores were −16.40 (−24.31, −8.49) at weeks 4 to 8 and −19.59 (−28.26, −10.92) at weeks 40 to 52; at weeks 40 to 52, changes were clinically meaningful in 84.6% of patients. Adjusted mean (95% CI) change from baseline to weeks 40 to 52 were 15.02 (7.35, 22.69), 19.37 (10.86, 27.89), 18.65 (7.44, 29.86), 9.85 (3.90, 15.81), and 16.09 (9.07, 23.11) for concern, coping, sleep, social interaction, and total, respectively. TS‐VAS, IPSS, and EQ‐5D‐5L all improved, and treatment persistence at weeks 40 to 52 was 77.1%. Urinary retention was reported in four (0.7%) patients. Conclusions: Vesomni was well‐tolerated and improved HRQoL and treatment satisfaction in patients with LUTS/BPH.